Firm Size as a Moderation Variable on The Effect of Inflation, Interest Rates, and Reputation of the Public Accounting Firm on Realized Stock Return - Steinly Sumendap; Jullie Sondakh; Heince Wokas (Dinasti Publisher, 2023)
Return and risk are two things that cannot be separated. Market risk in the capital market arises due to the changing economic conditions of a country. This study aims to determine the effect of inflation, interest rates and the reputation of a public accounting firm on realized stock returns with firm size as a moderating variable. This research was conducted on companies included in the LQ45 index from 2017 to 2021. The type of data used in this research is quantitative data with a total sample of 129 companies. Hypothesis testing was carried out using multiple linear analysis and Moderated Regression Analysis. The results show that partially inflation and interest rates affect the realized return of shares and the reputation of the public accounting firm has no effect on the realized return of the stock. Firm size does not moderate interest rates and the reputation of public accounting firms on realized returns, but moderates inflation because when inflation occurs, investors tend to invest in large companies because large companies are considered to be able to survive in inflationary conditions.